Collapse loading and energy absorption of fiber-reinforced conical shells. (1st June 2015) - Lin, J.S.; Wang, X.; Fang, C.Q.; Huang, X.
Abstract: Background/Purpose: An analytical solution is presented to predict the mean axial collapse forces of fiber reinforced conical shells under thermal loading, in which the fibers wrapped orientation is arbitrary; Methods: Analytical method and finite element simulate; Results: The influences of thermal loading, fibers wrapped orientations, geometrical eccentricity factor and proportionality coefficient on the axial collapse force of fiber reinforced conical shells are given. Conclusion: The collapse loading Pm of fiber-reinforced conical shells appears in the maximum value under different thermal environment when the fibers wrapped direction equals 45°. By optimizing the wrapping orientation of fiber layers, the capability of energy absorption of fiber-reinforced conical shells can be enhanced.